PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN NIAS SELATAN - Julianus Hulu (Universitas Nias Raya, 2026)
The goal of this study is to ascertain how employee performance at South Nias Regency Transportation Service is impacted by human resource development. It is an associative quantitative research design. Employees of the South Nias Regency Transportation Service are the source of the data. There were forty individuals working at the South Nias Regency Transportation Service Office, making up the sample for this study. Employees of the South Nias Regency Transportation Service are the responders to the questionnaires that are sent as part of the data gathering method. Simple regression analysis is the data analysis technique employed. The study's findings indicate that employee performance is impacted by HRD, as indicated by the computed t_value of 2.036, which is higher than the t_(table)= 1.689 value and the regression analysis's findings of Y = 35.455 + 0.356. The study's conclusion is that employee performance in the South Nias District Transportation Service is somewhat influenced by human resource development. According to the research, in order for employees to work effectively and professionally, the leadership of the South Nias Regency Transportation Service should be more cautious and truly selective when it comes to job rotations. Additionally, it is imperative that training sessions or job instruction exercises be held in order to provide employees with more work experience.